THE MAIN FACTORS COMPLEX CLASSIFICATION OF THE ENTERPRISE MANAGEMENT PROCESSES REENGINEERING - T. K. Abdullaeva; B. N. Gamidullaev; R. B. Gamidullaev (Вестник Дагестанского государственного технического университета: Технические науки)
Aim. The aim is to disclose and group the factors influencing the management processes reengineering at the enterprise.Methods. The paper is based on the methods of grouping, survey, system and logic analysis.Result. The complex of main factors reengineering which play a defining role in the management processes reengineering efficiency at the enterprise is systematized. The factors are given as four blocks on different activity directions stipulating high efficiency and enterprise development dynamics at any root reforms and management processes improvement. Special attention of the management processes reengineering efficiency is paid to personnel factors of reengineering success. A form of teaching as innovative-oriented individual retraining of specialists and executives of the enterprise with corresponding recommendations on the organization is proposed. The questionnaire has been worked out and the survey has been held to reveal the department manager’s work content.Conclusion. The main factors complex classification of the management processes reengineering at the enterprise creates a conceptual basis to provide efficiency of the management processes improvement methods at the enterprise.